Insecure and insensitive: Avoidant and anxious attachment predict less concern for others in sacrificial moral dilemmas. (February 2022) - Maranges, Heather M.; Chen, Susan K.; Conway, Paul
Abstract: Developmentally calibrated, adult attachment guides social decision making. We examined how insecure attachment styles relate to complex social decisions—moral dilemmas. Prior work failed to dissociate deontological (harm-rejecting) from utilitarian (outcome-maximizing) decisions, treating them as inversely related. Using process dissociation, we found avoidant attachment predicted less harm rejection—partially through lower empathic concern—whereas anxious attachment was not associated with moral responses across two samples (Study 1). Measuring attachment via inclusive multi-scale composites, we replicated the finding that people high in avoidance rejected harm less often, and also found that people high in anxious attachment rejected harm and maximized wellbeing less often (Study 2, preregistered). These relationships were mediated by lower empathic concern, lower desire to help others, and higher need to belong. Insecure attachment, whether avoidant or anxious, may distract from the emotional and moral concerns involved in avoiding harming others and increasing their wellbeing. Highlights: Prior work finds anxious and avoidant attachment predict utilitarian (U) decisions. Unlike that work, we use PD to dissociate U from deontological (D) decisions. Avoidant attachment predicts weaker D, not U, tendencies (Studies 1a & 1b). Via multiscale composites, anxious & avoidant attachment predict D & U (Study 2). The associations are mediated through lower empathic concern (Studies 1a, 1b, & 2).